Expert system diagnosing Android-based lung disease - Fahreza Ramadhan; Mochamad Alfan Rosid (Universitas Muhammadiyah Sidoarjo, 2019)
This research aims at the medical field utilizing technology to help improve better services to the wider community and be able to create an expert system to diagnose lung disease in children. This study uses the Dempster-Shaferke method in an expert system to diagnose lung disease in children. The lungs are respiratory organs associated with the circulatory system, the function of the lungs themselves is as a place of exchange of oxygen with carbon dioxide in the blood. The results of this study are expected to simplify the process of diagnosing lung disease in children, and also this expert system can help to ease the task of experts